Typification of the name Sedum monregalense (Crassulaceae) with notes on the correct publication date - Gallo, Lorenzo (Phytotaxa, 2017)
Sedum monregalense (Balbis, 1804: 339) is a well-known French-Italian endemic mountain taxon (Jalas et al. 1999: 104), described from plants collected in Piedmont (NW Italy) by I. Molineri (gardener at the Botanical Garden of Turin). However, a specimen of this taxon was already present in the herbarium of C. Allioni (1728–1804) stored at TO; the label reports the polynomial “Sedum montanum, tetraphyllum, floribus albis, foliis planis”. This name had been used by Tilli (1723: 157) and Micheli (1748: 88) who discovered this taxon in the Apennines (C Italy); however, Tilli (op.cit.) cited an earlier manuscript by Micheli named: “Catalogus Plantarum Agri Florentini” (cf. Parlatore 1844: 46). At last, it was already present in the Herbarium of U. Aldrovandi (1502–1605) (SMA Bologna 2017), there named “Sedum sive Sempervivum flore albo calice herbaceo sexaphyllo”.